Artemisia annua Leaf Extract Increases GLUT-4 Expression in Type 2 Diabetes Mellitus Rat - Arum Kartikadewi; Awal Prasetyo; Lisyani Budipradigdo; Heri Nugroho; Kusmiyati Tjahjono; Arthur Lelono (The Indonesian Biomedical Journal, 2019)
BACKGROUND: The depletion of glucose transporter 4 (GLUT-4) affects blood glucose level in the type 2 diabetes mellitus (T2DM) patient. Herbals supplementation such as Artemisia annua is known to posses an antidiabetic potency, but its effect on long term glucose control marker, glicated hemoglobin (HbA1C) and muscle GLUT-4 expression still has not been investigated.METHODS: Twenty Wistar rats were divided into four groups (five rats per group). The C1 group was consist of healthy control rats and C2 group was consist of diabetic control rats. Diabetic condition was induced by giving high lard fat diet for 28 days, followed with 30 mg/kgBW of Streptozotocin injection at the 29th day. Meanwhile, T1 and T2 group were consist of diabetic rats, which were supplemented with 50 mg/kgBW and 100 mg/kgBW of Artemisia annua leaf extract, respectively. GLUT-4 expression and HbA1C level were measured at the 14th day post-treatment.RESULTS: The GLUT-4 was expressed 1.8 and two times higher in T1 and T2 group, respectively, compared to C2 group. Meanwhile, HbA1C level in C2 group was two times higher than C1 group (11.95±2.52 compared to 5.61±2.69, p<0.01). Further, the administration of 100 mg/ kgBW Artemisia annua extract caused a slight reduction of HbA1C (11.95±2.52 compared to 8.18±3.53, p>0.05)CONCLUSION: Muscle cell’s GLUT-4 in T1 and T2 group was expressed increasingly and significantly different compared to the C2 group. HbA1C level in T2 was slightly reduced although no significant different compared to C2 group.KEYWORDS: Artemisia annua, GLUT-4, HbA1C, type 2 diabetes mellitus